Vulnerability of Rice Farmers to Climate Change in Kwara State, Nigeria - Sheu-Usman Oladipo Akanbi; Olanrewaju Solomon Olatunji; Olamide Sulaiman Oladipo; Uswat Temitayo Adeyemi; Akinyinka Akinyoade (Turkish Journal of Agriculture: Food Science and Technology)
Climate unpredictability and weather extremes are being projected as capable of presenting additional challenges for farmers currently engaged in the low-technology based food production systems in sub-Saharan countries like Nigeria. This study assessed rice farming households’ vulnerability to climate change in Kwara State, Nigeria. Primary data, collected from 150 respondents using simple random sampling procedure were analysed employing descriptive statistic was use to describe the coping strategies adopted and Human Development Index (HDI) was created to assess vulnerability of rice farmers to climate change. Statistical analyses indicated a vulnerability assessment index of 0.3001, pointing to a fact that the zone is prone to the adverse effects of climatic variability. For this reason, the study empirically underscores the need for farmers to adopt and adapt the planting of drought tolerant and/or early maturing varieties of rice. Importantly, the capacities of the local communities needs to be strengthened vis-à-vis the relationship between climate change and crop production. Capacity building at the farm level is crucial for improving crop, soil and water management, enhancing the demand for and use of better and more efficient production inputs. Tied to farm-level capacity building is the need to refocus public agricultural-based institutions towards exposing the rice farmers to effective mitigation strategies in the wake of climate change, provision of agricultural inputs, expansion of irrigation, efficient and effective extension service delivery, market development and other forms of necessary support.